Flubendazole demonstrates valid antitumor effects by inhibiting STAT3 and activating autophagy - Shichong Lin (Journal of Experimental & Clinical Cancer Research, 2019)
Abstract Background Signal transducer and activator of transcription 3 (STAT3) is an oncogene, which upregulates in approximately 70% of human cancers. Autophagy is an evolutionarily conserved process which maintains cellular homeostasis and eliminates damaged cellular components. Moreover, the STAT3 signaling pathway, which may be triggered by cancer cells, has been implicated in the autophagic process. Methods In this study, we found that the anthelmintic flubendazole exerts potent antitumor activity in three human colorectal cancer (CRC) cell lines and in the nude mouse model. The inhibition of cell proliferation in vitro by flubendazole was evaluated using a clonogenic assay and the MTT assay. Western blot analysis, flow cytometry analysis, siRNA growth experiment and cytoplasmic and nuclear protein extraction were used to investigate the mechanisms of inhibiting STAT3 signaling and activation of autophagy induced by flubendazole. Additionally, the expression of STAT3 and mTOR was analyzed in paired colorectal cancer and normal tissues collected from clinical patients. Results Flubendazole blocked the IL6-induced nuclear translocation of STAT3, which led to inhibition of the transcription of STAT3 target genes, such as MCL1, VEGF and BIRC5. In addition, flubendazole also reduced the expression of P-mTOR, P62, BCL2, and upregulated Beclin1 and LC3-I/II, which are major autophagy-related genes. These processes induced potent cell apoptosis in CRC cells. In addition, flubendazole displayed a synergistic effect with the chemotherapeutic agent 5-fluorouracil in the treatment of CRC. Conclusions Taken together, these results indicate that flubendazole exerts antitumor activities by blocking STAT3 signaling and inevitably affects the autophagy pathway. Flubendazole maybe a novel anticancer drug and offers a distinctive therapeutic strategy in neoadjuvant chemotherapy of CRC.